Endoscopic release of internal snapping hip: a review of literature - Via, Alessio Giai (Muscles Ligaments Tendons J, 2016)
BACKGROUND: Internal snapping hip is a common clinical condition, characterized by an audible or palpable snap of the medial compartment of the hip. In most cases it is asymptomatic, while in a few patients, mostly in athletes who participate in activities requiring extremes of hip range of motion, the snap may become painful (internal snapping hip syndrome - ISHS). MATERIALS AND METHODS: This is a review of current literature, focused on the pathogenesis, diagnosis and treatment of ISHS. CONCLUSION: The pathogenesis of ISHS is multifactorial, and it is traditionally believed to be caused by the tendon snapping over the anterior femoral head or the iliopectineal ridge. Most cases of ISHS resolve with conservative treatment, which includes avoidance of aggravating activities, stretching, and NSAIDs. In recalcitrant cases, surgery may be indicated. Better results have been reported with endoscopic iliopsoas tendon release compared with open techniques, which may be related to the treatment of concomitant intra-articular pathologies. Furthermore, endoscopic treatment showed fewer complications, decreased failure rate and postop erative pain. It is important to remember that in most cases, a multiple iliopsoas tendon may exist, and that the incomplete release of the iliopsoas tendon can be a reason for refractory pain and poor results. Then, even if of not clinical relevance at long term follow-up, patients should be told about the inevitable loss of flexion strength after iliopsoas tenotomy. LEVEL OF EVIDENCE: II.